Joint effects of sodium intake and circadian rhythm of urinary sodium excretion on prognosis of chronic kidney disease: a prospective study - Yu He; Jiawen Li; Jialing Rao; Weiyan Lai; Qin Wei; Haiteng Li; Yuxuan Li; Hui Peng; Jun Zhang (Therapeutic Advances in Chronic Disease)
Background: Sodium harmony is closely correlated with the progression of chronic kidney disease (CKD). Objectives: The current study aims to explore the significance of the circadian rhythm of urinary sodium excretion in CKD management and to help establish individualized salt restriction strategies. Design: This is a prospective study among inpatients with CKD. Methods: The study included 715 participants with CKD from the Third Affiliated Hospital of Sun Yat-Sen University. Multivariable Cox regression models and restricted cubic splines were employed to explore the independent and joint associations of 24-h urinary sodium and sodium rhythm with prognosis of CKD. Results: During a median follow-up of 6.92 years, 286 major renal events, 112 MACE, 160 deaths, and 321 composite events were documented. 24-h urinary sodium was not associated with any outcomes. However, there were dose–response associations of diurnal sodium/24-h urinary sodium with major renal events ( p overall  < 0.001, p nonlinearity  = 0.016) and composite events ( p overall  < 0.001, p nonlinearity  = 0.129). Compared with the combination of low 24-h sodium and normal sodium rhythm, the combination of high 24-h sodium and abnormal sodium rhythm had the highest risk of incident major renal events (hazard ratio, 1.62; 95% confidence interval, 1.04–2.51). A significant interaction was observed between sodium intake and sodium rhythm in associations with composite events ( p for interaction = 0.015). Conclusion: The circadian rhythm of sodium excretion emerges as a novel and potentially more sensitive risk factor for the prognosis of CKD. Furthermore, the association between sodium intake and progression of CKD was notably pronounced among individuals with abnormal sodium rhythms. Efforts to implement individualized salt restriction strategies are warranted.